Challenges in the translation of legal texts: the case in Kosovo - Sopjani, Valentina; Hamiti, Vjosa (Comparative Legilinguistics, 2023)
Our paper conducts a contrastive analysis between Albanian and English lexical units in the language of laws using corpora analysis. It fills a literature gap related to Corpus linguistics in order to better comprehend patterns of legal lexicon. We use KWIC Concordance to extract the top frequently words and concordance lines in order to analyse differences and similarities among lexical units in Albanian (Source Language) and English (Target Language) laws, compared to those identified in respective corpora. Additionally, we identify types of errors in translation, difficulties in translating legal texts, and factors that influence translators’ errors in translating certain laws of the Republic of Kosovo from Albanian into English. According to our analysis, both languages have in common the use of the same grammatical patterns such as: conjunctions, prepositions, and the use of the common noun forms. The rest have significant differences in their usage, especially with regards to particles and determiners. Our contrastive approach demonstrates that some of these laws were not originally written in Albanian and then translated into English language, as many articles within these laws lack the appropriate word structure and word order and in some cases are semantically ill-formed in the Source Language.